Parabolically induced unitary representations of the universal group U(F)^+ are C_0 - Ciobotaru, Corina (MATHEMATICA SCANDINAVICA, 2019)
We prove that all parabolically induced unitary representations of the Burger-Mozes universal group U(F)^+, with F being primitive, are C_0. This generalizes the same well-known result for the universal group U(F)^+, when F is 2-transitive.